Sustainable Release of Vancomycin from Silk Fibroin Nanoparticles for Treating Severe Bone Infection in Rat Tibia Osteomyelitis Model - Hassani Besheli, N. (2017)
The successful treatment of bone infections is a major challenge in the field of orthopedics. There are some common methods for treating bone infections, including systemic antibiotic administration, local nondegradable drug vehicles, and surgical debridement, and each of these approaches has advantages and disadvantages. In the present study, the antibiotic vancomycin (VANCO) was loaded in silk fibroin nanoparticles (SFNPs) and the complexes were then entrapped in silk scaffolds to form sustained drug delivery systems. The release kinetics of VANCO from SFNPs alone and when the SFNPs were entrapped in silk scaffolds were assessed at two different pH values, 4.5 and 7.4, that affected the release profiles of VANCO. Disk diffusion tests performed with pathogens causing osteomyelitis methicillin-resistantÂ Staphylococcus aureus(MRSA) showed antibacterial activity of the released drug at two different pH values. Additionally, injection of 8 Ã 106Â CFU MRSA in ratâ s tibia induced severe osteomyelitis disease. Radiographic and histopathological analyses were performed to evaluate the effectiveness of treatment after 6 weeks. The VANCO-loaded silk fibroin nanoparticles entrapped in scaffolds reduced bone infections at the defected site with better outcomes than the other treatment groups. In conclusion, the delivery system with good biocompatibility and sustained release properties would be appropriate for further study in the context of osteomyelitis disease.